2022
DOI: 10.1371/journal.pone.0265601
|View full text |Cite
|
Sign up to set email alerts
|

Health status of street children and reasons for being forced to live on the streets in Harar, Eastern Ethiopia. Using mixed methods

Abstract: Introduction In Ethiopia, more than four million children are anticipated to live under particularly difficult circumstances. Street children are subject to violence, a lack of health care, and a lack of education. Which denies them the right to live in a secure environment and exposes them to different health problems. Currently, little is known about the prevalence of Streetism, including health conditions. Therefore, this study was aimed to assess the health status of street children and determinants of Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Furthermore, these reasons can vary depending on whether children are in industrial or developing countries [ 6 ]. Specifically, many global and local studies in countries, including India, Bangladesh, Namibia, Botswana, Cameroon, Democratic Republic of Congo, Egypt, Ethiopia, Ghana, Kenya, Nigeria, Rwanda, Senegal, South Africa, Sudan, Tanzania, Tunisia, Uganda, and Zimbabwe, have identified poverty as the most common reason [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ], along with family problems and breakdown, parental deaths, social and cultural norms, displacement due to natural disasters and conflict, domestic violence, child neglect and abuse, inadequate education, legal systems, and peer pressure [ 5 , 8 , 10 , 11 , 12 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, these reasons can vary depending on whether children are in industrial or developing countries [ 6 ]. Specifically, many global and local studies in countries, including India, Bangladesh, Namibia, Botswana, Cameroon, Democratic Republic of Congo, Egypt, Ethiopia, Ghana, Kenya, Nigeria, Rwanda, Senegal, South Africa, Sudan, Tanzania, Tunisia, Uganda, and Zimbabwe, have identified poverty as the most common reason [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ], along with family problems and breakdown, parental deaths, social and cultural norms, displacement due to natural disasters and conflict, domestic violence, child neglect and abuse, inadequate education, legal systems, and peer pressure [ 5 , 8 , 10 , 11 , 12 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in different countries, including Indonesia, Bangladesh, Nepal, and several African countries, reveal that discrimination subjects street children to hunger, malnutrition, body pains, sickness, and exhaustion; furthermore, they are frequently exposed to injuries, burns, accidents, and polluted environments, and they also experience lower academic achievement [ 10 , 11 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In terms of mental health, evidence from Ethiopia, Ghana, Kenya, Vietnam, South Africa, and India shows that street children experience poor mental health and face challenges such as high levels of stress, anti-social behavior, anxiety, aggression, and depression [ 6 , 11 , 21 , 26 , 27 , 28 ], and they consume drugs and alcohol [ 11 , 29 , 30 , 31 ]. Furthermore, they experience sexual abuse, violence, and risk behaviors that could increase the risk of sexually transmitted infections [ 5 , 6 , 11 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, homosexuality and intergenerational sex are prevalent among street children (Alidost et al, 2021;Chikoko, Ruparanganda, Muzvidziwa, & Chimhowa-Chikoko, 2018;Chikoko, Ruparanganda, Muzvidziwa, & Chimhowa-Chikoko, 2019;Kayombo, 2020). As a result, infectious diseases (STIs and HIV) are prevalent among street children (Abate et al, 2022;Martin, 2018;Strashun et al, 2020). In terms of how they respond to the abuse, the majority of them reported that they did not take any action after being raped because they believe that reporting would have no effect on their experience with the situation (Kelly & Karsna, 2017).…”
Section: Introductionmentioning
confidence: 99%